Passengers' Perceptions Towards Air-Conditioned Buses in Nepal (Kaladarpan कलादर्पण, 2023)
In order to promote social and environmental causes, bus services are extremely important. In order to raise productivity, promote economic growth, and improve access to mar- kets and services, transportation infrastructure and services should be expanded. This includes the creation of air-conditioned buses. The objective of the study is to understand how passengers feel about traveling in air-conditioned buses in Nepal. The descriptive type of research methodology was used to conduct the study. Reliability, responsibility, empathy, tangibility, and assurance are the five aspects used to evaluate a company's performance in providing services. Majority of respondents were dissatisfied with bus crew's ability to provide accurate bus arrival times and an- swer questions. 83.33 % of respondents replied that chairs of buses are comfortable to sit on. Re-garding safe traveling and trustworthiness many of the respondents are satisfied with the bus staff.